PENDAPAT HUKUM TENTANG PEMBENTUKAN “KAMPUNG RESTORATIVE JUSTICE” DI KABUPATEN - Patiwi, Frida (Fakultas Hukum Universitas Narotama, 2025)
“Kampung Restorative Justice” is a community-based initiative to resolve criminal cases through mediation and dialogue rather than punishment, aiming to restore relationships between perpetrators, victims, and the community. This approach emphasizes peaceful settlement through mutually agreed resolutions, education to raise awareness of restorative principles, and prevention by encouraging accountability and rehabilitation. Implementation typically involves community leaders or neutral mediators, active community participation, and prioritizing out-of-court settlements for minor cases such as theft, assault, or traffic violations. Despite challenges like limited public understanding, differing views among law enforcement, and lack of facilities, this initiative offers a promising pathway to create a fairer, victim-centered, and sustainable justice system at the village level. Keywords: Restorative Justice Village, Government, Gresik